COMPREHENSIVE STUDY OF GREEN SUKUK FUNCTION IN CREATING GOLDEN INDONESIA 2045 - Sarkowi, Sarkowi; Laksono, Muflih Adi; Asbullah, M.; Hartika, Ika; Nurnaningsih, Rita (JURNAL ILMIAH EDUNOMIKA, 2024)
ABSTRACT This study is a qualitative study with a descriptive approach. The data used in the article used is secondary data that researchers obtain from various credible sources. The sources that researchers mean are sources that are commonly used in every study, namely scientific articles, scientific magazines, books, and various other sources. The data is obtained through the stages of data collection, data reduction, data selection, and drawing conclusions. The rsult in this article show that Green Sukuk and Indonesia Emas have the same straight line to support each other to achieve existing goals. From the four points presented in the previous paragraph, there is a point of superior civilized human resources. One of the characteristics of superior civilization is that people invest more often with sukuk instruments than spending on unproductive consumption. Thus, it can be concluded that Green Sukuk can contribute to creating Indonesia Emas 2045. Keywords: Green Sukuk, Golden Indonesia, 2045